Kedai Kopi Modern: (Perancangan Bisnis Kedai Kopi) - Agung Wijoyo; Fathul Ghina; Reza Alif Anugrah; Dwi Nur Febriyanto; Munandar (OKTAL : Jurnal Ilmu Komputer dan Sains, 2022)
This business plan is entitled modern coffee shop. The main purpose of this business planning is to open up great business opportunities with workers to be as creative as possible and provide quality coffee offerings and utilize coffee produced by coffee farmers in Indonesia which is very abundant and diverse in its types. with affordable prices among millennials, because for now coffee lovers are more dominant among millennials and students, before opening a coffee shop business we must survey the coffee lovers who are dominant among millennials and students. With affordable prices among millennials, because for now coffee lovers are more dominant among millennials and students, before opening a coffee shop business we must survey the place or location that we will open later so that it is not misplaced and does not harm entrepreneurs in the long run, for the convenience of customers this coffee shop will be built with a modern theme such as the existence of adequate facilities such as Wifi, sufficient parking space, and an air-conditioned and clean room so that customers do not doubt the food and beverage menu that will be sold. From the point of view of entrepreneurs, coffee shops are mostly for socializing centers that provide a place to gather, read and entertain each other in these social groups, besides selling coffee, modern coffee shops also sell various foods and drinks such as martabak, toast, juice, noodles, fried foods and cold drinks.